2017
DOI: 10.1007/s00784-017-2196-x
|View full text |Cite
|
Sign up to set email alerts
|

Bond durability of universal adhesive to bovine enamel using self-etch mode

Abstract: The present data indicate that the enamel bond durability of universal adhesives in the self-etch mode might be sufficient for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…Regarding the bond strength against water, saliva or blood contamination, there are studies in support of different results. Some studies state no significant difference in dry or wet condition 11,25,26,30 . But some studiesfound low shear bond strength of conventional and hydrophilic primer containing bonding agents, especially when contamination occurred before and/or after priming.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the bond strength against water, saliva or blood contamination, there are studies in support of different results. Some studies state no significant difference in dry or wet condition 11,25,26,30 . But some studiesfound low shear bond strength of conventional and hydrophilic primer containing bonding agents, especially when contamination occurred before and/or after priming.…”
Section: Resultsmentioning
confidence: 99%
“…So, contamination of enamel with saliva after priming decreased the bond strength although it was still clinically adequate. As for universal adhesive systems, Suzuki et al 30 showed that they were not affected by water contamination (both thermocycled group and long-time water stored group). Nevertheless, Cartas et al 31 experimented the action of alcoholic beverage on bonding agents and detected that bonding strength varied with the solution used.…”
Section: Effect Of Saliva Contamination and Thermocyclingmentioning
confidence: 99%
“…Universal adhesives represent the last generation of adhesives, which can be used with different modes 21,27,28 . Various studies have investigated universal adhesives' enamel bond strength 18,20 . To the best of our knowledge, no study had been performed evaluating the bond strength values to laser-assisted bleached enamel using universal adhesive systems.…”
Section: Discussionmentioning
confidence: 99%
“…With a single bottle performing two different strategy of bonding, these adhesives are very cost effective. 16 Although many in vitro studies had been conducted to assess the bond strength of universal adhesives [17][18][19][20][21] , to the extent of authors' knowledge no study has examined the effects of pre-restorative Diode Laserassisted bleaching on enamel bond strength of universal adhesives. As bleaching has become a routine treatment in clinics, it is important to find out which application mode would enhance the bonding ability of different universal adhesives to laser-bleached enamel.…”
mentioning
confidence: 99%
“…The result of this study showed that the overall ability of universal adhesive bonding is significantly higher than that of other bonding, although the type of substrate is also effective in bond strength. Inversely, in the study of Suzuki et al, 30 the shear bond strength of universal adhesives (including Scotchbond Universal, G-Premio bond, and All-bond Universal) with a conventional two-step self-etch adhesive, Clearfil SE bond was investigated. The result shows that the shear bond strength of universal adhesives was significantly lower than two-step self-etch adhesive.…”
Section: Discussionmentioning
confidence: 99%